Aβ (Amyloid Beta) and Tau Tangle Pathology Modifies the Association Between Small Vessel Disease and Cortical Microinfarcts. Issue 3 (11th February 2021) - Kapasi, A.; Leurgans, S.E.; Arvanitakis, Z.; Barnes, L.L.; Bennett, D.A.; Schneider, J.A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: There is increasing recognition of the importance of cortical microinfarcts to overall brain health, cognition, and Alzheimer dementia. Cerebral small vessel pathologies are associated with microinfarcts and frequently coexist with Alzheimer disease; however, the extent to which Aβ (amyloid beta) and tau pathology modulates microvascular pathogenesis is not fully understood. Study objective was to examine the relationship of small vessel pathologies, arteriolosclerosis, and cerebral amyloid angiopathy, with cortical microinfarcts in people with differing levels of Aβ or tau tangle burden. Methods: Participants were 1489 autopsied older people (mean age at death, 89 years; 67% women) from 1 of 3 ongoing clinical-pathological cohort studies of aging. Neuropathological evaluation identified cortical Aβ and tau tangle burden using immunohistochemistry in 8 brain regions, provided semiquantitative grading of cerebral vessel pathologies, and identified the presence of cortical microinfarcts. Logistic regression models adjusted for demographics and atherosclerosis and examined whether Aβ or tau tangle burden modified relations between small vessel pathologies and cortical microinfarcts. Results: Cortical microinfarcts were present in 17% of older people, moderate-to-severe cerebral amyloid angiopathy pathology in 36%, and arteriolosclerosis in 34%. In logistic regression models, we found interactions with Aβ and tau tangles, reflecting that the association between arteriolosclerosis and cortical microinfarcts was stronger in the context of greater Aβ (estimate, 0.15; SE=0.07; P =0.02) and tau tangle burden (estimate, 0.13; SE=0.06; P =0.02). Interactions also emerged for cerebral amyloid angiopathy, suggesting that the association between cerebral amyloid angiopathy and cortical microinfarcts is more robust in the presence of higher Aβ (estimate, 0.27; SE=0.07; P <0.001) and tangle burden (estimate, 0.16; SE=0.06; P =0.005). Conclusions: These findings suggest that in the presence of elevated Aβ or tangle pathology, small vessel pathologies are associated with greater microvascular tissue injury, highlighting a potential link between neurodegenerative and vascular mechanisms.